The influence of smart mother classes toward stress, childbirth self-efficacy and birth outcomes - Runjati Runjati; Sri Rahayu; Dhita Aulia Octaviani (International Journal of Public Health Science (IJPHS), 2022)
Coping efforts during pregnancy are significant in influencing better pregnancy and birth outcomes. This study aimed to prove the influence of smart mother classes (SMC) on stress, childbirth self-efficacy (CBSE), and birth outcomes. This research used an experimental design, pre and post-test control group design. The population was all pregnant women at 28-35 weeks of pregnancy in Semarang City, Indonesia. The sample was chosen by cluster random sampling, where 35 health centers in 12 regions were randomized as six regions (n=60) as intervention group (antenatal class and coping skill as smart mother classes) while the other six regions (n=60) as the control group (antenatal class only). Each region runs one class with 10 pregnant women. The groups were treated four times in four weeks. The measurement was before the treatment, fourth week, and at birth. This study used repeated-measures ANOVA. The results showed that the SMC was influenced significantly in reducing stress (p=0.012), and increasing CBSE but not statistically significant (p>0.05). The SMC also had a significant impact on the outcomes of birth (p<0.05), except the time of the first stage of labor (p>0.05). The study suggested a need for the provision of continuity and holistic midwifery care.